A Plant Cryptochrome Controls Key Features of the Chlamydomonas Circadian Clock and Its Life Cycle. Issue 1 (30th March 2017) - Müller, Nico; Wenzel, Sandra; Zou, Yong; Künzel, Sandra; Sasso, Severin; Weiß, Daniel; Prager, Katja; Grossman, Arthur; Kottke, Tilman; Mittag, Maria
Abstract : A plant cryptochrome has multiple roles within the circadian clock and the sexual cycle of a unicellular photosynthetic organism. Abstract: Cryptochromes are flavin-binding proteins that act as blue light receptors in bacteria, fungi, plants, and insects and are components of the circadian oscillator in mammals. Animal and plant cryptochromes are evolutionarily divergent, although the unicellular alga Chlamydomonas reinhardtii ( Chlamydomonas throughout) has both an animal-like cryptochrome and a plant cryptochrome (pCRY; formerly designated CPH1). Here, we show that the pCRY protein accumulates at night as part of a complex. Functional characterization of pCRY was performed based on an insertional mutant that expresses only 11% of the wild-type pCRY level. The pcry mutant is defective for central properties of the circadian clock. In the mutant, the period is lengthened significantly, ultimately resulting in arrhythmicity, while blue light-based phase shifts show large deviations from what is observed in wild-type cells. We also show that pCRY is involved in gametogenesis in Chlamydomonas . pCRY is down-regulated in pregametes and gametes, and in the pcry mutant, there is altered transcript accumulation under blue light of the strictly light-dependent, gamete-specific gene GAS28 . pCRY acts as a negative regulator for the induction of mating ability in the light and for the loss of mating ability in the dark. Moreover, pCRY is necessary for light-dependent germination, during which the zygote undergoes meiosis that gives rise to four vegetative cells. In sum, our data demonstrate that pCRY is a key blue light receptor in Chlamydomonas that is involved in both circadian timing and life cycle progression.